2016
DOI: 10.1093/femsec/fiw151
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale assemblage of an ectomycorrhizal fungal community: the influence of host functional traits and soil properties in a 10-ha miombo forest

Abstract: Ectomycorrhizal fungi (EMF) are highly diversified and dominant in a number of forest ecosystems. Nevertheless, their scales of spatial distribution and the underlying ecological processes remain poorly understood. Although most EMF are considered to be generalists regarding host identity, a preference toward functional strategies of host trees has never been tested. Here, the EMF community was characterised by DNA sequencing in a 10-ha tropical dry season forest-referred to as miombo-an understudied ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 88 publications
3
29
0
Order By: Relevance
“…Responses of symbiotic fungi to host species and habitat specialization are corroborated in several other studies on host identity: Bauman et al. () found that plant traits explained up to 11% of ectomycorrhizal community variation. Öpik et al.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Responses of symbiotic fungi to host species and habitat specialization are corroborated in several other studies on host identity: Bauman et al. () found that plant traits explained up to 11% of ectomycorrhizal community variation. Öpik et al.…”
Section: Discussionsupporting
confidence: 55%
“…For example, plants may exert influence outside the rhizosphere via microbe-microbe interactions (e.g., through mycorrhizal fungi) or plant-litter feedback that modifies the local environment (Mart ınez-Garc ıa, Richardson, Tylianakis, Peltzer, & Dickie, 2015; Urbanova, Snajdr, & Baldrian, 2015). Similarly, studies that have measured plant traits and soil microbial communities in parallel find that plant functional diversity, traits and habitat specialization can explain soil microbial community diversity, richness and composition (Bauman et al, 2016;Chagnon, Bradley, & Klironomos, 2015;Lang, Seven, & Polle, 2011;Nguyen, Williams, et al, 2016;€ Opik, Metsis, Daniell, Zobel, & Moora, 2009;Sikes, Cottenie, & Klironomos, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bauman et al. () have shown spatial correlations between mycorrhizal community and soil properties in our study site. The three genera in this study ( Combretum, Strychnos, Ziziphus ) are known to host endomycorrhizae (Bâ, Duponnois, Diabaté, & Dreyfus, ; Högberg, ; Högberg & Piearce, ).…”
Section: Discussionsupporting
confidence: 55%
“…Other mutually non-exclusive mechanisms that may explain the poor survival of matrix species on termite mounds include pathogenic microorganisms and mycorrhizal symbionts. Bauman et al (2016) have shown spatial correlations between mycorrhizal community and soil properties in our study site. The three genera in this study (Combretum, Strychnos, Ziziphus) are known to host endomycorrhizae (Bâ, Duponnois, Diabaté, & Dreyfus, 2011;Högberg, 1982;Högberg & Piearce, 1986).…”
Section: Journal Of Vegetation Sciencementioning
confidence: 54%
“…1) can then be used 1) as predictors to study the multiscale spatial patterns of the response data (e.g. species abundances; Declerck et al 2011, Bauman et al 2016, Vleminckx et al 2017), or 2) as covariables (spatial filters) to remove spatial autocorrelation from residuals (spatial eigenvector mapping, SEVM; Griffith 2003, Diniz-Filho and Bini 2005, Dormann et al 2007, Bini et al 2009, Corkeron et al 2011. However, all eigenvector-based methods, including MEM, face a common issue.…”
Section: Introductionmentioning
confidence: 99%